A Study on Enhancing the Properties of Geopolymer Concrete Using Hybrid Fibers - Varouqa, Ibrahim Farouq (International Journal of Membrane Science and Technology, 2024)
Alkali is present in significant quantities in geopolymer concretes. Due of this, their ductility and flexural strength are also low. The flexural strength of concrete is enhanced by the addition of fibers. Flexural strength has been a challenge for geopolymer concretes, thus researchers have tried using fibers to strengthen them. On the other hand, geopolymer concretes have never before utilized hybrid fibers. This study is an effort to incorporate hybrid fibers in geopolymer concrete to prevent its brittle fracture. Experiments are conducted to learn more about the geopolymer concrete’s different mechanical characteristics, and then the settings are fine-tuned. Mechanical qualities of geopolymer concrete are improved by determining the optimal molarity of sodium hydroxide, the optimal ratio of sodium silicate to sodium hydroxide, and the optimal proportion of addition of fibers.